Economic development, the nutrition trap and metabolic disease - Nancy Luke; Kaivan Munshi; Anu Mary Oommen; Swapnil Singh (Yale University, Economic Growth Center, 2021)
This research provides a single explanation for: (i) the persistence of malnutrition and (ii) the increased prevalence of metabolic disease (diabetes, hypertension, cardiovascular disease) among normal weight individuals with economic development. Our model is based on a set point for BMI or bodyweight that is adapted to conditions of scarcity in the pre-modern economy, but which subsequently fails to adjust to rapid economic change. During the process of development, some individuals thus remain at their low-BMI set point, despite the increase in their consumption, while others who have escaped the nutrition trap (but are not necessarily overweight) are at increased risk of metabolic disease. The model and the underlying biological mechanism, which are validated with micro-data from India, Indonesia and Ghana can jointly explain inter-regional (Asia-Africa) differences in nutritional status and the prevalence of diabetes.
Keywords: 330; Entwicklung; Ernährungspolitik; Chronische Krankheit; Faktorenanalyse